2020
DOI: 10.3389/fmicb.2020.506068
|View full text |Cite|
|
Sign up to set email alerts
|

Isolation and Characterization of a Novel Myophage Abp9 Against Pandrug Resistant Acinetobacater baumannii

Abstract: Acinetobacter baumannii (A. baumannii) has emerged as one of the most troublesome pathogens in health care institutions. A. baumannii can cause a wide range of diseases in humans, including pneumonia and septicemia. Phage therapy has drawn great interest from medical researchers as a potential way to control infections by antibioticresistant A. baumannii. Using a pandrug-resistant clinical A. baumannii isolate AB ZY 9 as an indicator, we isolated a lytic phage Abp9 from hospital sewage. Abp9 belongs to myoviri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Studies in murine models are particularly often described, including in the case of bacterial infections and phage therapy used against them. Many different routes of administration of bacteriophages or their enzymes can be used in mice, for example, intranasally or intratracheally in the case of pneumonia [54,[57][58][59][60], intraperitoneally or intramuscularly in the case of sepsis [55,[61][62][63], intraperitoneally or/and topically in the case of wound infection [59,64], by injection into subcutaneous pockets in the case of a wound infection sustained during catheterization [65], and topically to the corneal surface in the cases of eye infections [66,67]. The advantages and disadvantages of different routes of phages or phage enzyme administration are presented in Table 1.…”
Section: Usefulness Of Animal Models and Their Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in murine models are particularly often described, including in the case of bacterial infections and phage therapy used against them. Many different routes of administration of bacteriophages or their enzymes can be used in mice, for example, intranasally or intratracheally in the case of pneumonia [54,[57][58][59][60], intraperitoneally or intramuscularly in the case of sepsis [55,[61][62][63], intraperitoneally or/and topically in the case of wound infection [59,64], by injection into subcutaneous pockets in the case of a wound infection sustained during catheterization [65], and topically to the corneal surface in the cases of eye infections [66,67]. The advantages and disadvantages of different routes of phages or phage enzyme administration are presented in Table 1.…”
Section: Usefulness Of Animal Models and Their Limitationsmentioning
confidence: 99%
“…A mouse model of systemic infection caused by A. baumannii and the applied phage therapy was described by Jiang et al [61]. Immediately after intraperitoneal administration of bacterial suspension, mice were injected with the first dose of the bacteriophage suspension (5.0 × 10 8 PFU) by the same route.…”
Section: Animal Models Of Acinetobacter Baumannii Infectionmentioning
confidence: 99%
“…(2016) suggested that phage‐mediated eradication as well as disinfection of biofilms formed on metal surfaces is more difficult than that of biofilms in a liquid environment. The phage Abp9 effectively cleared ABZY9‐produced biofilms in vitro and in mice infection model reducing mortality in the latter (Jiang et al ., 2020).…”
Section: Single Phage Therapy/monophage Therapy Against a Baumanniimentioning
confidence: 99%
“…Phage‐derived depolymerases have the unique ability to recognize and degrade capsule polysaccharides, EPS and O‐antigen and thus, present a promising tool in the therapeutics as well as diagnostics (Latka et al ., 2017). Depolymerases degrade components of the biofilm exopolymeric matrix enabling the phages to infect the inner cells of biofilms (Jiang et al ., 2020).…”
Section: Phage‐encoded Enzyme Therapeutics Against a Baumanniimentioning
confidence: 99%
“…In previous studies, we have successfully isolated podoviridae phage Abp1 from hospital sewage, and its treatment effect was tested in a local and system mouse model of infection [12]. Using a drug-resistant A. baumannii strain ABzy9 separate from a patient's femoral venous catheter, and we also isolated a myoviridae phage Abp9 that cleaves ABzy9 [13]. Abp9 can effectively remove the bio lm produced by ABzy9 and reduce the mortality rate of rats infected with ABzy9.…”
Section: Introductionmentioning
confidence: 99%